Interpretation of airborne radiometric data of flamingo field, Southwestern Nigeria - T. O Lawal; O. Fawale; J. A. Sunday; G. B. Egbeyale (Journal of Nigerian Society of Physical Sciences)
The airborne radiometric data of the Flamingo Field, Southwest Nigeria has been analyzed and interpreted with the aim of evaluating the surface geology and structural features that are critical for mineral resource exploration. The objectives of the study are to delineate the alteration zones by correlating interpreted data with the lithological units, and to describe the relationship between the airborne radiometric anomalies and the subsurface structural trends. To achieve this, the data was subjected to rigorous qualitative and quantitative interpretation. Maximum and minimum concentration values for Total count (TC (Unit of radiation (Ur)) rate, Potassium (K %), equivalent of Thorium (eTh) and that of Uranium (eU) were estimated. The results of the study show that the  value of Ur, K, eTh%, and eU in Flamingo Field range from 2.408 to  41.017, 0.162 to 3.238 (%), 0.846 to 33.104 (ppm) and 0.169 to 7.232 (ppm), respectively. Locations of the associated anomalies which serve as alteration zones were obtained and values obtained from this expression clearly reveals that majority of the rock units for most of the radio elements in the area  are below one hundred percent, while few others such as carbonaceous/slate phyllite, meta siltstone, undifferentiated schist and granite gneiss have values above 100%, especially for potassium and thorium elements. Also, the produced composite radioelements and image maps reveals bright some zones within the field which is a revelation of anomalous alteration zones. More so, the most prominent trend in the field correspond to the Northeast -- Southwest and Northwest -- Southeast directions which plays an important role in the structural framework of the study area.